EXTRACTABLE SILICON AND IRON STATUS OF SOME SOUTHWESTERN NIGERIAN SOILS - ASHAYE, T. I.; PERIASWAMY , S. P.; AMUSAN, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Citric acid extractable silicon (CAES) and iron (CAEI) in selected Southwestern Nigerian soils which differ in drainage and parent materials were investigated. The CAES and CAEI the soils increase with increasingly poor drainage. The CAES in the well-drained soils or the sedimentary environment is lower than those from the metamorphic area. The amount of CAEI present and its distribution appears abundant for most crops. The CAES of the whole profile in the study area could be predicted from that of surface horizon, The common soil units in the study area. Ferric Luvisols, Eutric Gleysols and Vertic Cambisols had averages of 169, 210 and 373 ppm CAES respectively.